Effect of different parameters controlling the flexural behavior of RC beams strengthened with NSM using nonlinear finite element analysis (Fracture and Structural Integrity, 2020)
Near surface mounted technique become the most attractive technique for strengthening RC structures. Several researches had been conducted to study experimentally the flexural behavior of RC members strengthened with NSM technique unlike the numerical researches. In this paper a numerical investigation utilizes the non-linear finite element (FE) modeling using ANSYS was performed. The developed FE model considers the behavior of the epoxy-concrete interface using a particular continuum damage approach, called cohesive zone model (CZM) which is capable of predicting the failure mode of the strengthened beams. The modified model study the effect of different parameters such as NSM bar number, NSM bar length, end inclination angle and end inclination leg length on the flexural behavior of strengthened beams. The results showed that, The developed FE model able to predict the expected modes of failure in NSM technique, the NSM bar length was effective till 0.5 of beam span, beams strengthened with end inclined angle 45º NSM bar gives the highest improvement in load carrying capacity, this improvement was very close in case of using end inclined angle of 60º and 90º.
Keywords: Finite Element Modeling; Near Surface Mounted; Debonding; End Anchorage; Inclination Angle; Flexural Strengthening